SPE California Regional Meeting 1982
DOI: 10.2118/10701-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of In-Situ Combustion in Diatomites

Abstract: Diatomaceous sediments of California host large reserves of oil and gas tut are incompletely exploited. The matrix of these sediments is comprised largely of the frustules of diatoms (microscopic marine plants). Punctae in the frustules are responsible for the high porosities Punctae in the frustules are responsible for the high porosities characteristic of diatomites (up to 70 vol.%), but because of the very small size of the pores, permeabilities are low (commonly around 1 md). Furthermore, the oil contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Craig and Parrish (1974) concluded that reservoir heterogeneities such as natural reservoir-scale fractures can lead to poor combustion efficiency. Fassihi et al (1982) reported that the bypassing and fingering of oxygen/air that arises from reservoir heterogeneities leads to low-temperature oxidation (LTO) reactions downstream of the combus-614 S. M. Fatemi et al tion. Schulte and De Vries (1985) observed that the process was governed by diffusion of oxygen from fissures into the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Craig and Parrish (1974) concluded that reservoir heterogeneities such as natural reservoir-scale fractures can lead to poor combustion efficiency. Fassihi et al (1982) reported that the bypassing and fingering of oxygen/air that arises from reservoir heterogeneities leads to low-temperature oxidation (LTO) reactions downstream of the combus-614 S. M. Fatemi et al tion. Schulte and De Vries (1985) observed that the process was governed by diffusion of oxygen from fissures into the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A combustão é controlada pela reação química ou pela difusão? Alguns investigadores (Dabbous et al, 1974; descobriram que a combustão é controlada pela difusão, enquanto que outros descobriram que é controlada pela reação química ( Hughes et al, 1987;Fassihi e Brigham, 1982;Burger, 1976). Islam et al, 1989, contestaram que os experimentos de laboratório sejam conduzidos em condições ideais, onde a taxa de transferência de massa do oxigênio é alta, e a influência da difusão é mascarada.…”
Section: Equacionamento Primáriounclassified